PENGARUH DISKON, E-WOM DAN GENDER TERHADAP PEMBELIAN IMPULSIF PRODUK KULINER SECARA ONLINE PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - Difana, Dhevika Thentaria; Pradikto, Sugeng; Suchaina, Suchaina (STIE Semarang, 2024)
This study aims to determine how much influence partially or simultaneously from the variables of discounts, e-WOM, and gender on Impulsive Purchases of Culinary Products Online on Economic Education Students at PGRI Wiranegara University. Food delivery service applications that are often used by consumers are applications such as Gofood, Grabfood, Shopeefood. When buying food or drinks, customers can buy easily and practically thanks to the growing food delivery service. Impulse purchases can occur suddenly, one of which triggers the desire to buy goods without planning or spontaneously, namely the existence of discounts or discounts given. This study uses quantitative research methods, data collection using a questionnaire or questionnaire distributed to 72 respondents. Data processing using the SPSS version 25 application. The data analysis technique consists of validity test, reliability test, descriptive analysis, classical assumption test, multiple linear regression test and hypothesis testing. The results showed that (1) there is a partial effect of discounts on impulse purchases of culinary products online on Economic Education Students of PGRI Wiranegara University (2) there is a partial effect of e-WOM on impulse purchases of culinary products online on Economic Education Students of PGRI Wiranegara University. (3) there is a partial influence of Gender on impulsive purchases of culinary products online on Economic Education Students of PGRI Wiranegara University (4) there is a simultaneous influence of discounts, e-WOM and Gender on impulsive purchases of culinary products online on Economic Education Students of PGRI Wiranegara University.